(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Gone are the days when “Might is Right”, the law of Jungle use to prevail everywhere, though it still exists but to a much lesser degree. This means that the people & nations have understood their duties & right towards others in the current information or precisely the media age. This would not have come to the existence in the absence of the revolutionary nature of the computer evolution (encompassing almost all the disciplines of life) either Relativism or Emotivism paradigm. In my opinion Ethics is” Acknowledgement of others rights (whosoever & whatsoever) is directly or indirectly related to you & discharging your duties and responsibilities to them to the utmost satisfaction of your inner self. ” This research based on the lifelong (twenty eight years ) teaching the software Engineering as a computer discipline has envisioned the researcher to attribute software Engineering as a character in the light of the various ethical and moral considerations , theory and Practices.